2021
DOI: 10.1371/journal.pone.0248479
|View full text |Cite
|
Sign up to set email alerts
|

Ayurveda botanicals in COVID-19 management: An in silico multi-target approach

Abstract: The Coronavirus disease (COVID-19) caused by the virus SARS-CoV-2 has become a global pandemic in a very short time span. Currently, there is no specific treatment or vaccine to counter this highly contagious disease. There is an urgent need to find a specific cure for the disease and global efforts are directed at developing SARS-CoV-2 specific antivirals and immunomodulators. Ayurvedic Rasayana therapy has been traditionally used in India for its immunomodulatory and adaptogenic effects, and more recently ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 90 publications
(96 reference statements)
0
29
0
1
Order By: Relevance
“…Ltd. as a gift. We have used standardized extracts prepared as per previously reported method ( Borse et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ltd. as a gift. We have used standardized extracts prepared as per previously reported method ( Borse et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To date, several studies have begun to look at the active compounds found in medicinal plants used in Traditional medicine since many of them have a long history of antiviral activity [ 290 , 296 , 298 , 299 , 300 , 301 , 302 ]. Numerous groups have used in silico computational approaches, drug-like filters, and toxicity studies to screen small drug-like molecules from a dataset of phytochemicals with antiviral activities [ 299 ], and the number of multi-target natural compounds were predicted to suppress the activity of three or more major drug targets simultaneously [ 296 , 301 , 303 , 304 ]. Thus, compounds that targeted five, four, and three drug targets and exerted anti-COVID-19 activities by multi-component and multi-target action were found in the studies of B Naik et al (2020) and L-Q Gao (2020) [ 296 , 303 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Columbin is a diterpenoid furanolactone; it displays anti-inflammatory, anti-cancer, and antioxidant activity, protects from azoxymethane-induced rat colon carcinogenesis and possess a trypanocidal mechanism [25,26]. Hence, T. cordifolia has been drawn interest in research as a COVID-19 preventive measure [27,28].…”
Section: Introductionmentioning
confidence: 99%